Evaluation of women with postcoital bleeding by clinical examination, papsmear, colposcopy and histopathology of cervix - Yarlagadda, Srilakshmi; Diddi, Rangarao; Narra, Prasuna J. L. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Postcoital bleeding refers to spotting or bleeding per vagina that occurs after intercourse and is not related to menstruation. Although there are multiple benign etiologies to this complaint, the most serious cause of postcoital bleeding is cervical cancer (3-5.5%). Cervical cancer is the most common and preventable genital cancer of women. It has a long premalignant phase and with an ideal screening test with good sensitivity and specificity, we can diagnose and treat premalignant cervical lesions, preventing cervical cancer. The present study is aimed to evaluate the women with postcoital bleeding by clinical examination, pap smear, colposcopy and guided biopsy to detect premalignant cervical lesions and carcinoma cervix. Methods: This was a prospective and retrospective study conducted from April, 2016 to March, 2018 for a period of 24 months in the Department of Obstetrics and Gynaecology on 100 women with postcoital bleeding at Dr. Pinnamaneni Siddhartha Institute of Medical Sciences and Research Foundation (Dr. PSIMS&RF). After clinical examination, these women were subjected to pap smear, colposcopy and guided biopsy. The findings were correlated with histopathology of cervix. The sensitivity, specificity, positive predictive value, negative predictive value and accuracy of both papsmear and colposcopy were calculated. Results: Sensitivity of papsmear was 71.42%, specificity-86.20%, PPV-78.95%, NPV-80.64% and accuracy-80%. Sensitivity of colposcopy was 90.47%, specificity-89.65%, PPV-86.36%, NPV-92.85% and accuracy-90%. Conclusions: These results establish colposcopy as an effective screening test for carcinoma cervix. Histopathology of suspected cervical lesion in colposcopy remains the gold standard for definitive diagnosis.